Cannabis-Induced Hypodopaminergic Anhedonia and Cognitive Decline in Humans: Embracing Putative Induction of Dopamine Homeostasis - Blum, Kenneth; Khalsa, Jag; Cadet, Jean Lud; Baron, David; Bowirrat, Abdalla; Boyett, Brent; Lott, Lisa; Brewer, Raymond; Gondré-Lewis, Marjorie; Bunt, Gregory; Kazmi, Shan; Gold, Mark S. (Frontiers in Psychiatry, 2021)
Over the years, the regular use of cannabis has substantially increased among young adults, as indicated by the rise in cannabis use disorder (CUD) with an estimated prevalence of 8.3% in the United States. Research shows that exposure to cannabis is associated with hypodopaminergic anhedonia (depression), cognitive decline, poor memory, inattention, impaired learning performance, reduced dopamine brain response-associated emotionality, and increased addiction severity in young adults. There is increasing concern by the addiction medicine community because of the high content of delta-9-tetrahydrocannabinol (THC) currently found in oral and vaping cannabis products, the cognitive effects of cannabis may become more pronounced in young adults who use these cannabis products. Preliminary research suggests that it is possible to induce 'dopamine homeostasis,' that is, restore dopamine function with dopamine upregulation with the proposed compound and normalize behavior in chronic cannabis users with cannabis-induced hypodopaminergic anhedonia (depression) and cognitive decline. This psychological, neurobiological, anatomical, genetic, and epigenetic research also could provide evidence to develop an appropriate policy regarding decriminalization, but not legalization, of cannabis for recreational use.